Tomorrow's organization - Mohrman, Susan Albers (Jossey-Bass business & management series, 1998)
"Based on eighteen years of in-depth research conducted with Fortune 1000 companies by the Center for Effective Organizations, Tomorrow's Organization is the first book to offer specific hands-on solutions and practical guidelines for creating organizations that can complete successfully in the twenty-first century." "From issues of strategy and structure to leadership and capability development, the authors combine their research and consulting experience to offer the latest thinking and emerging practices today's most successful companies have incorporated to achieve strategic market advantage. And they outline the flatter, more flexible and dynamic designs these companies have instituted. Tomorrow's Organization describes how to design for the new competitive environment - including customer product structures, design issues in networked organizations, and the structuring of global organizations. The contributors reveal which current practices are most likely to prove of lasting value and offer new ways to manage employees through competency-based pay, the new learning contract, and new approaches to executive development. They also provide guidelines for implementing technology as a critical underpinning of new organizational forms."--Jacket.